The Effectiveness of Virtual Tour Museums on Student Engagement in Social Studies Learning in Elementary Schools - Ariesta, Freddy Widya; Maftuh , Bunyamin; Sapriya; Syaodih , Ernawulan (Universitas Pendidikan Ganesha, 2024)
During the era of digital transformation, the integration of technology into the field of education through teaching methods has become a necessity. This study aims to measure the effectiveness of museum virtual tour media on increasing student involvement in social studies learning in elementary schools. Research design uses quasi-experiment with pre-test and post-test control-group design. The research sample consisted of 64 students in the fifth grade. The dimensions and indicators used in the questionnaire are sourced from The Student Engagement in School Questionnaire (SESQ). The data used in this research comes from questionnaires, interviews, and documentation. The N-gain Score test was chosen to analyse the data, comparing the average scores between the experimental and control groups. The findings show that there is a disparity in the average engagement results between students who use virtual museum tour media and students who use traditional textbooks. The experimental class obtained an n-gain score of 0.683 which indicated an increase in student involvement in the high category, while the control class obtained an n-gain score of 0.193 which indicated an increase in student involvement in the low category. Thus, the use of virtual museum tour media is proven to be able to make a significant contribution in increasing student involvement, encouraging cultural appreciation, and strengthening students' sense of nationalism in elementary schools.